Thomas Holcroft's revolutionary drama : reception and afterlives - Garnai, Amy, 1957- (Lewisburg, Pennsylvania : Bucknell University Press, 2023)
A key figure in British literary circles following the French Revolution, novelist and playwright Thomas Holcroft promoted ideas of reform and equality informed by the philosophy of his close friend William Godwin. Arrested for treason in 1794 and released without trial, Holcroft was notorious in his own time, but today appears mainly as a supporting character in studies of 1790s literary activism. Thomas Holcroft's Revolutionary Drama authoritatively reintroduces and reestablishes this central figure of the revolutionary decade by examining his life, plays, memoirs, and personal correspondence. In engaging with theatrical censorship, apostacy, and the response of audiences and critics to radical drama, this thoughtful study also demonstrates how theater functions in times of political repression. Despite his struggles, Holcroft also had major successes: this book examines his surprisingly robust afterlife, as his plays, especially The Road to Ruin, were repeatedly revived worldwide in the nineteenth century.
Thomas Holcroft and the treason trials -- The road to ruin and its afterlives -- Radicalism, authorship and sincerity in Holcroft's later plays -- Holcroft's diary and other life writing -- Holcroft's melodrama -- Final years and other afterlives.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Holcroft, Thomas, -- 1745-1809 -- Criticism and interpretation; Holcroft, Thomas, -- 1745-1809 -- Influence; Holcroft, Thomas, -- 1745-1809; English drama -- 18th century -- History and criticism; Théâtre anglais -- 18e siècle -- Histoire et critique; PERFORMING ARTS / General; English drama; Influence (Literary, artistic, etc.); 1700-1799; Thomas Holcroft, Treason Trials, melodrama, theater censorship, working-class life writing, William Godwin, Sir Thomas Lawrence, James Gillray, Robert Dighton, Richard Newton, Samuel de Wilde, William Mulready, radicalism, authorship, life writing, afterlives, The Road to Ruin, eighteenth-century theater, nineteenth-century theater, theater and performance, literary activism, 1790s, radical drama, eighteenth-century political activism; Criticism, interpretation, etc